2012
DOI: 10.1165/rcmb.2012-0241oc
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Second-Hand Smoke Aggravates Adult Responses to Irritants

Abstract: In utero exposure to second-hand smoke (SHS) is associated with exacerbated asthmatic responses in children. We tested the hypothesis that in utero SHS will aggravate the lung responses of young adult mice re-exposed to SHS. We exposed Balb/c mice in utero to SHS (S) or filtered air (AIR; A), and re-exposed the male offspring daily from 11-15 weeks of age to either SHS (AS and SS) or AIR (AA and SA). After the adult exposures, we analyzed samples of bronchoalveolar lavage fluid (BALF), examined the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…The low correlation (Pearson's r 5 0.1, between RNA-seq and microarray) and more blue dots scattered near the vertical line (x 5 0) in panel B&C, indicated that the RNA-seq had better sensitivity, particularly among low abundance genes (lowest 25%, in blue dots). our lab Rouse et al, 2007;Xiao et al, 2012], the effects of in utero SHS followed by no subsequent adult exposure to any environmental agent produces very few differences (notably in BALF cytology) between the in utero SHS-exposed mice compared to air controls. Mice exposed in utero to air or SHS exhibit similar responses at 15 and 23 weeks of age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The low correlation (Pearson's r 5 0.1, between RNA-seq and microarray) and more blue dots scattered near the vertical line (x 5 0) in panel B&C, indicated that the RNA-seq had better sensitivity, particularly among low abundance genes (lowest 25%, in blue dots). our lab Rouse et al, 2007;Xiao et al, 2012], the effects of in utero SHS followed by no subsequent adult exposure to any environmental agent produces very few differences (notably in BALF cytology) between the in utero SHS-exposed mice compared to air controls. Mice exposed in utero to air or SHS exhibit similar responses at 15 and 23 weeks of age.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we reported that in utero second-hand smoke (SHS) exposure aggravates adult responses to subsequent post-natal exposures to environmental irritants, including ovalbumin (OVA) Xiao et al, 2013] and SHS [Xiao et al, 2012]. In the most recent studies [Xiao et al, 2013], where we challenged all adult mice with OVA to induce allergic asthma, we found that the effects of in utero SHS exposure persisted into adulthood, further aggravated lung inflammation, elevated Th2 cytokine levels in bronchoalveolar lavage fluid (BALF), increased airway hyperresponsiveness (AHR), and altered gene expression profiles (microarray-based).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted SHS exposures on BALB/c mice (Harlan, Indianapolis, IN), as described previously (3,11). Briefly, half of the mated females, randomly selected, were exposed to SHS generated from 3R4F filtered research cigarettes (10 mg/m 3 ; University of Kentucky, Lexington, KY) mixed with AIR daily, from Days 6 to 19 of gestation.…”
Section: Animal Protocols Shs and Ova Exposuresmentioning
confidence: 99%
“…This was performed as described previously (3,11). For each mouse at each methacholine dose level (3-50 mg/ml), readings over 5 minutes were averaged for Penh and f. Penh values represent the degree of AHR in each animal.…”
Section: Pulmonary Function Testingmentioning
confidence: 99%
See 1 more Smart Citation